2011
DOI: 10.1007/s00432-011-1117-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transcatheter arterial chemoembolization and microsphere embolization for treatment of unresectable hepatocellular carcinoma: a meta-analysis

Abstract: These data demonstrated that microsphere embolization treatment of patients with surgically unresectable HCC provided much better survival and treatment response than that of TACE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…showed a significantly longer time to progression with TARE than with TACE. A meta‐analysis of retrospective studies from Xie et al . demonstrated a survival benefit of TARE over TACE [HR: 0.73 (95% CI: 0.60–0.88); P = 0.0009].…”
Section: Resultsmentioning
confidence: 99%
“…showed a significantly longer time to progression with TARE than with TACE. A meta‐analysis of retrospective studies from Xie et al . demonstrated a survival benefit of TARE over TACE [HR: 0.73 (95% CI: 0.60–0.88); P = 0.0009].…”
Section: Resultsmentioning
confidence: 99%
“…One meta-analysis compared the outcomes of TACE versus microsphere embolization [123]. Microsphere embolization was superior to TACE in terms of OS, TTP, and tumor response [123].…”
Section: Tacementioning
confidence: 99%
“…Microsphere embolization was superior to TACE in terms of OS, TTP, and tumor response [123]. In the subgroup analyses, the benefit was statistically significant in patients undergoing 32 P glass microspheres, but not in those undergoing 90 Y microspheres.…”
Section: Tacementioning
confidence: 99%
“…in unresectable HCC showed that radioembolisation was significantly better for OS, 1 year survival and TTP compared with TACE. There was a tendency toward a higher response rate in radioembolisation compared to TACE …”
Section: Comparison Of Transcatheter Therapiesmentioning
confidence: 99%